FRAMING THE RISK OF ISLAMIC BASED EQUITY FINANCING: AN INSIDE LOOK - Adawiyah, Wiwiek Rabiatul (Al-Ulum, 2015)
This article is a review of the literature that aims at bringing into surface the issue of risk management in equity-based financing which is currently less attractive to Islamic banks. There are several forms of Islamic financing offered to potential borrower. Equity financing is less favorable as compared to debt financing due to high risks associated with it. Substantial numbers of strategies have been developed by researchers to mitigate the financing risks nonetheless the attempt is far from succeed. It is evidenced in the literature that both investors and financial intermediaries tend to overlooked profit and loss sharing mode of financing.  Meanwhile Equity financing is adored to be the best form of financing to be offered to small business since it is operating under the principle of justice.  Profit and loss sharing mechanism relieve both fund providers and borrowers from financial burden.  This article shall review potential risks embedded in equity financing and strategies to overcome the problem. -----Artikel ini merupakan kajian literatur yang bertujuan untuk membahas manajemen resiko bagi pembiayaan syariah berbasis ekuitas yang saat ini kurang diminati oleh bank syariah.  Bank syariah menawarkan beberapa bentuk pembiayaan kepada calon nasabah. Pembiayaan berbasis bagi hasil dianggap kurang menguntungkan dibandingkan dengan pembiayaan berbasis hutang karena adanya risiko tinggi terkait pembiayaan bagi hasil. Sejumlah strategi telah dikembangkan oleh peneliti untuk meminimalisir resiko pembiayaan namun strategi tersebut masih jauh dari sukses karena belum mampu meningkatkan jumlah pembiayaan berbasis bagi hasil yang disalurkan oleh bank syariah. Meskipun demikian pembiayaan syariah berbasis ekuitas dianggap sebagai bentuk terbaik dari pembiayaan yang akan ditawarkan kepada usaha kecil karena beroperasi atas prinsip keadilan. Mekanisme pembiayaan berbasis laba rugi meringankan pihak yang bermitra, dalam hal ini bank Islam dan usaha kecil, dari beban keuangan. Artikel ini akan meninjau potensi risiko yang melekat pada pembiayaan ekuitas dan strategi untuk mengatasinya